Evaluasi Praktik Pengalaman Lapangan Mahasiswa Universitas Sunan Giri Surabaya Terhadap Al-Hadits Sebagai Sumber Ilmu Dalam Islam - Amatillah Thaha; Muhammad Yusron Maulana El-Yunusi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Field Experience Practice (PPL) is a medium for applying basic knowledge for students studying with a concentration majoring in Islamic Religious Education in the Postgraduate program. To apply basic knowledge as prospective lecturers, it is necessary to hold field experience practice (PPL) at universities that are in accordance with respective concentration or expertise. Field Experience Practice (PPL) activities include learning and educational management practices with the aim of increasing students' understanding and analysis of Al-Hadith as a source of knowledge in Islam. The theory obtained in learning can be implemented well and effectively in this Field Experience Practice activity. The deficiencies and obstacles that occur can be overcome with solutions that are considered to be easily implemented by lecturers and students so that this PPL activity has a positive impact on lecturers and students. The benefit of this PPL activity is apart from learning, it is also gaining experience in administration and management so that this PPL helps improve the quality and quality of Islamic Religious Education postgraduate students in developing students' abilities (competencies) pedagogically, professionally, personally and socially and lecturers will automatically be helped by the activity PPL in optimizing student learning activities.